A cserebogarak (Melolonthidae) elleni gombaszuszpenziós (Beauveria) védekezés hatékonysága - Horváth Eszter (2017)
In European forest management the harm caused by Melolonthidae species is a major issue. As biological protection gains space new methods and substances are to be used and examined. One of these is the treatment with species of the entomopathogenic fungus Beauveria that is already studied for decades. In our experiment we treated 4 Beauveria strains of two species with 4 different chemicals that are generally used in forestry nurseries. These chemicals are: Taifun 360, Basudin, Vegesol eReS and Topaz. Comparing the growth rate of the treated strains with those of the controll ones it occurs that among the used chemicals only the fungicidal Topaz had major influence on the growth rate of the srains. On fields and woodlots where Beauveria species are used it is feasible not to use fungicide chemicals.